STRATEGI MANAJEMEN PERUBAHAN DALAM MENGHADAPI TRANSFORMASI DIGITAL: STUDI KASUS PADA PERUSAHAAN FUJI FILM - Pujiastuti Ramadhani, Novi; Haludin, Guntur; Tri Bawono, Galih; Angelika Sumardi, Rizqi; Fitriyani, Desy; Wirakusuma , Agung; Luhung, Ili (Bussman Journal : Indonesian Journal of Business and Management, 2024)
Digital transformation has become imperative for company survival in the modern era. This study analyzes the change management strategies implemented by Fuji Film in facing digital transformation through a systematic literature review approach. Using content analysis of academic literature from 2020-2024, this research reveals how Fuji Film successfully transformed from a traditional photography company into an innovative technology company. The results show that Fuji Film’s digital transformation success was supported by three key elements: comprehensive change management strategy, systematic digital capability development, and structured technology implementation. The company adopted the "Digital Transformation Triangle" model integrating technology, process, and human resources, supported by strong transformational leadership and continuous investment in digital talent development. This transformation resulted in significant increases in digital revenue and operational effectiveness. This research greatly advances our knowledge of change management techniques in the context of digital transformation and provides valuable lessons for traditional companies undergoing similar processes